Fifteen-Year Surveillance of LTR Receiving Pre-Emptive Therapy for CMV Infection: Prevention of CMV Disease and Incidence of CLAD - Davide Piloni; Elisa Gabanti; Monica Morosini; Gabriela Cassinelli; Vanessa Frangipane; Federica Zavaglio; Tiberio Oggionni; Laura Saracino; Sara Lettieri; Eloisa Arbustini; Federica Meloni; Daniele Lilleri (Microorganisms, 2022)
The efficacy of pre-emptive therapy in the prevention of cytomegalovirus (CMV) disease and the potential association of CMV infection with the occurrence of chronic lung allograft dysfunction (CLAD) was evaluated in 129 lung transplant recipients receiving pre-emptive therapy based on pp65-antigenemia or CMV-DNA in the blood and in the bronchoalveolar lavage. Seventy-one (55%) patients received pre-emptive ganciclovir/valganciclovir (GCV/VGCV) for CMV infection for a median of 28 (9–191) days. Possible CMV disease occurred in six (5%) patients and was healed after the GCV/VGCV therapy. The cumulative incidence of CLAD was 38% and 54% at 5 and 10 years. Acute rejection and CMV load in the blood (but not in the lung) were independent predictors of the occurrence of CLAD. Pre-emptive therapy is highly effective in preventing CMV disease in lung recipients and does not induce a superior incidence of CLAD compared to what reported for other cohorts of patients who received an extended antiviral prophylaxis.